Discovery of Novel Striatal‐enriched Protein Tyrosine Phosphatase Inhibitors Through Structure‐based Virtual Screening. (12th October 2016) - Ku, Bonsu; You, Jin A; Lee, Hye Seon; Shin, Ho‐Chul; Park, Hwangseo; Kim, Seung Jun
Abstract : Striatal‐enriched protein tyrosine phosphatase (STEP) is considered a potential target for the development of therapeutics for neurodegenerative diseases and cocaine addiction. We herein report 10 novel STEP inhibitors identified using a combination of in silico structure‐based virtual screening with an accurate solvation free energy term‐applied improved scoring function and in vitro phosphatase inhibition assay. These compounds, computationally selected for their advantageous physicochemical properties as drug candidates, exhibited micromolar IC50 values of 3.21–10.6 μM. Enzyme kinetic assays together with structure‐based docking simulations suggested that three most potent inhibitors are novel surrogates for phosphotyrosine that are accommodated at the active site of STEP. We expect that identification of these compounds will provide a foundation for further improvement and optimization to develop STEP‐targeting drug candidate molecules. Abstract :